On the interaction between product markets and markets for production capacity: The case of the electricity industry - Jan Richter (Institute of Energy Economics at the University of Cologne (EWI), 2012)
We study the interdependency between two markets, where the first involves offering production capacity, while on the second actual production is sold. The key issue is that the expected product market outcome determines the opportunity cost for bidding at the capacity market while the capacity sold on the capacity market, since no longer available for spot market bidding, influences the product market outcome. We show that a competitive simultaneous equilibrium exists. This equilibrium is unique and efficient. It is characterized by a u-shaped bidding function in the capacity market with respect to the marginal cost of suppliers. The leading example is the electricity industry, where there is a capacity market clearing before the spot market.
Keywords: D41; D44; L11; L94; 330; capacity market; procurement auction; electricity market; competitive equilibrium